2020
DOI: 10.2147/ibpc.s265183
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Hypertensive Emergency and Associated Factors Among Hospitalized Patients with Hypertensive Crisis: A Retrospective Cross-Sectional Study</p>

Abstract: Background: Hypertensive emergency (HE) is an acute stage of uncontrolled blood pressure which poses a substantial cardiovascular morbidity and mortality in developing countries. In our setting, the prevalence of HE and the characteristics of patients with a hypertensive crisis are not certainly known yet. Objective: The study assessed the prevalence of hypertensive emergency and associated factors among hospitalized patients with hypertensive crisis. Methods: A retrospective cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
0
21
1
1
Order By: Relevance
“…In Africa, including SSA, data on in‐hospital, as well as the long‐term, outcomes of HE are limited 22,23 . In Ethiopia, uncontrolled BP is increasing with an estimated pooled prevalence of 48% (95% confidence interval [CI]: 36–61) 24 and it is as high as 57.2% at the Jimma Medical Center (JMC), 25 which increases hypertensive‐related organ damages and mortality 26,27 . Despite an increment in the prevalence of uncontrolled BP in Ethiopia, only a few studies reported admission outcomes of HE 11,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, including SSA, data on in‐hospital, as well as the long‐term, outcomes of HE are limited 22,23 . In Ethiopia, uncontrolled BP is increasing with an estimated pooled prevalence of 48% (95% confidence interval [CI]: 36–61) 24 and it is as high as 57.2% at the Jimma Medical Center (JMC), 25 which increases hypertensive‐related organ damages and mortality 26,27 . Despite an increment in the prevalence of uncontrolled BP in Ethiopia, only a few studies reported admission outcomes of HE 11,26 .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In Ethiopia, uncontrolled BP is increasing with an estimated pooled prevalence of 48% (95% confidence interval [CI]: 36-61) 24 and it is as high as 57.2% at the Jimma Medical Center (JMC), 25 which increases hypertensive-related organ damages and mortality. 26,27 Despite an increment in the prevalence of uncontrolled BP in Ethiopia, only a few studies reported admission outcomes of HE. 11,26 Therefore, the primary aim of this study was to evaluate in-hospital mortality and its associated factors of HE.…”
Section: Introductionmentioning
confidence: 99%
“…In chest pain is the most frequent clinical presentation of hypertensive emergency, 4 others conveyed dyspnea as the commonest clinical presentation of hypertensive emergency. 8,[14][15][16] Grasping Hypertensive emergency clinical context is crucial for its recognition. Our result helped in clarifying hypertensive emergency clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…На пике лихорадки повышение АД является следствием спазма периферических сосудов, а в период критического падения температуры за счет вазодилатации, повышенного диуреза АД снижается и может привести к возникновению гипотонии вплоть до коллапса. Выраженные неконтролируемые колебания АД ассоциируются с высоким риском развития сердечно-сосудистых осложнений (ССО) у пациентов с АГ, в первую очередь инсульта и острого коронарного синдрома [48]. В настоящее время известно, что течение COVID-19 может сопровождаться гипертермией от субфебрильных до гиперпиретических цифр.…”
Section: течение аг на фоне Covid-19 аг и лихорадочные состоянияunclassified